The Practice of Equal Inheritance Distribution in Karangbanyu Village, Ngawi - Setiawan Bin Lahuri; Fina Nurafni; Alfan Jawahir Muhammad (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study explores the practice of inheritance distribution between men and women, where the majority of the community applies an equal 1:1 division rather than the 2:1 ratio prescribed in Islamic inheritance law. While the Qur’an establishes the 2:1 distribution as just and beneficial (maṣlaḥah), reflecting the distinct rights and responsibilities of men and women, the community interprets justice as equal shares. Factors influencing this practice include customary traditions, parental instructions, the desire to avoid family disputes, the longer caregiving role often carried out by daughters, and the perception that all children deserve equal rights. This research uses a qualitative juridical-sociological approach, drawing data from interviews, documentation, and supporting literature. The findings indicate that the 1:1 practice is viewed locally as fair and beneficial because it prevents conflict, maintains family harmony, and ensures individual ownership of assets. However, from the perspective of Islamic law, true maṣlaḥah lies in the 2:1 provision, which balances men’s financial duties with women’s honored but non-financial roles. The study highlights the tension between local customs and Islamic legal principles, suggesting the need for broader awareness and dialogue to align community practices with the objectives of the Sharī‘ah